2022
DOI: 10.3390/su14073900
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Loan Acquisition and Utilization among Smallholder Rice Producers in Lagos State, Nigeria

Abstract: Agriculture is a major contributor to economic development in most developing nations, with smallholder farmers playing a critical role, but their productivity and growth are impeded by a lack of access to agricultural loans. The affordability of loans is critical for sustainable agricultural development. Therefore, this paper investigates farmers’ loan acquisition and utilization, as well as their choice of loan sources using a two-part model and multinomial logit model. A total of 281 smallholder rice farmer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…It also concludes that there is a need to adapt bank lending policies to farmers' different socio-economic and agricultural characteristics. Ameh and Lee (2022) found that annual farm income and interest rate positively impact loan access, while education, farming experience, farm size, off-farm income, and farm income significantly move loan use. Kadanalı and Kaya (2020) argued that one of the principal instruments in agricultural financing is agricultural lending.…”
Section: Agricultural Loans-a Literature Reviewmentioning
confidence: 99%
“…It also concludes that there is a need to adapt bank lending policies to farmers' different socio-economic and agricultural characteristics. Ameh and Lee (2022) found that annual farm income and interest rate positively impact loan access, while education, farming experience, farm size, off-farm income, and farm income significantly move loan use. Kadanalı and Kaya (2020) argued that one of the principal instruments in agricultural financing is agricultural lending.…”
Section: Agricultural Loans-a Literature Reviewmentioning
confidence: 99%
“…Larger household sizes may result to increase expenditure in the provision of social welfare (Ameh and Lee, 2022). Similarly, a study on household size by Liqiong et al (2019) in China showed that household size affected household income, credit and influenced agricultural loans accessibility.…”
Section: Socio-economic Characteristics Of Farmersmentioning
confidence: 99%
“…An agricultural loan is a financial service rendered to farmers for the purpose of production, processing, marketing and the like 1 . It includes institutional (formal) and non-institutional (informal) sources and the duration can be short, medium or long-term.…”
Section: Introductionmentioning
confidence: 99%